PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN DI UD. ELVIN KECAMATAN LAHUSA KABUPATEN NIAS SELATAN - Dede Putra Wau (Universitas Nias Raya, 2023)
The purpose of this study is to determine the effect of product and service quality on customer satisfaction at UD. Elvin, Lahusa District, South Nias Regency. The source of the data was from consumers, with the population and sample in this study being 34 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is multiple linear regression analysis. The results of this study showed that the Fhitung value was 60,958>Fttable of 3,305. This research can be concluded that there is a positive and significant influence on product and service quality on consumer satisfaction at UD. Elvin, Lahusa District, South Nias Regency. The suggestions for this study are (1) Preferably UD. Elvin can group products that are old or close to expiration with new products so that consumer satisfaction increases when making purchases. (2) In increasing customer satisfaction, employees should provide good service to consumers through a friendly attitude so that consumers are loyal in place.